DIFFERENCES IN HEMOGLOBIN LEVELS OF CONVENTIONAL SMOKERS AND MIXED SMOKERS (CONVENTIONAL AND ELECTRIC) - Dadang Muhammad Hasyim, Dadang Muhammad Hasyim; Dina Nirwana Suwinda, Dina Nirwana Suwinda; Gina Nafsa Mutmainna, Gina Nafsa Mutmainna (Jurnal Medika Farmaka, 2023)
Smoking is one of the biggest concerns in the world of health today because until now cigarettes are still the main cause of death and disease. Conventional cigarettes are processed tobacco products that are wrapped in paper to form cylinders. Vape is an alternative to conventional cigarettes allegedly safer than conventional cigarettes. Research This study aims to determine the difference in hemoglobin levels of conventional smokers and mixed smokers (conventional and electric). Qualitative method with comparative survey technique. The samples in this study were conventional smokers and mixed smokers. Consisting of 30 samples, 15 samples of conventional smokers and 15 samples of mixed and used smokers. The results of independent t test. The value of Sig. (2 tailed) of 0.018 more than 0.05, then there is a significant (significant) difference between the hemoglobin (hb) of conventional smokers and mixed smokers. Further research can continue research in analytical form with different, specific and more developed parameters. Comparison of hemoglobin levels in conventional smokers and mixed smokers, and pay attention to the brand in e-cigarettes (vapor).